Combining Action Research With Design Science as a Qualitative Research Methodology. An Application to Service (Operations) Management Research - Valeria de Castro; María Luz Martín-Peña; Esperanza Marcos Martínez; Maricela Salgado (International Journal of Qualitative Methods)
Services currently represent most of the present economic activity. Research methodologies that allow organisations to solve their service operations-related problems while facilitating the design and creation of new artefacts with which to support the complex reality that services represent are required. Action Research (AR) is a methodology that has proved to be effective in organisations by solving real problems. This methodology can be enriched with others that provide practical and usable solutions. This paper presents Design Science Action Research (DSAR), a methodology that combines AR and Design Service Research (DSR) and examines its usefulness for Service (Operation) Management research by supporting the development of new artefacts acting in the real context of organisations. DSAR has been applied in a case study concerning a service company that is addressing the transformation of its service design and delivery processes. We contribute to the literature on AR and DSR with a new methodology resulting from the combination of both approaches that can be used in order to conduct SOM research. We provide step-by-step guidance on its application and discuss the main advantages of using this combination in a real case.